#### Answer

$${a_1} = \frac{2}{3},{a_2} = 4,{a_3} = 24$$

#### Work Step by Step

$$\eqalign{
& {a_1} = \frac{2}{3},\,\,\,\,r = 6,\,\,\,\,n = 3 \cr
& {\text{The general term of a geometric sequence is }}{a_n} = a{r^{n - 1}}.{\text{ with first term }}a{\text{ and }} \cr
& {\text{common ratio }}r. \cr
& {\text{substituting }}{a_1} = \frac{2}{3},\,\,\,\,r = 6{\text{ into }}{a_n} = a{r^{n - 1}}{\text{ to obtain}} \cr
& {a_n} = \left( {\frac{2}{3}} \right){\left( 6 \right)^{n - 1}} \cr
& {\text{list the }}n = 3{\text{ terms}}{\text{. then}} \cr
& {a_1} = \frac{2}{3} \cr
& {a_2} = \left( {\frac{2}{3}} \right){\left( 6 \right)^{2 - 1}} = \left( {\frac{2}{3}} \right)\left( 6 \right) = 4 \cr
& {a_3} = \left( {\frac{2}{3}} \right){\left( 6 \right)^{3 - 1}} = \left( {\frac{2}{3}} \right){\left( 6 \right)^2} = 24 \cr
& \cr
& {\text{then}} \cr
& {a_1} = \frac{2}{3},{a_2} = 4,{a_3} = 24 \cr} $$